Tissue Factor Pathway Inhibitor: New Insights into an Old Inhibitor - Adams, Murray (Seminars in Thrombosis and Hemostasis, 2012)
Blood coagulation in vivo is triggered by the tissue factor (TF) pathway. The major physiological regulator of this pathway is tissue factor pathway inhibitor (TFPI), a Kunitz-type inhibitor that regulates the activity of the TF-factor VIIa complex in a factor Xa-dependent manner, thus controlling the generation of thrombin and ultimately, fibrin. Although some of the in vivo and in vitro effects of TFPI have been described for nearly a century, the bulk of the research that has elucidated the physiology of this inhibitor has only occurred in the past 25 years. Despite this, many questions remain. This review will highlight the recent advances in knowledge related to TFPI, with an emphasis on new insights into its physiology, association with disease, and possible use as a therapeutic anticoagulant.
Keywords: tissue factor; tissue factor pathway inhibitor; thrombosis; protein S; platelets